The medical record: confidentiality, access and disclosure (1992)
The CMA affirms that medical records are confidential documents. Although the records are the property of the physician or health care institution that compiled them, patients have a right to examine their records and to copy information contained in them. Physicians should provide an explanation of the medical record to the patient when requested to do so. Unless the law requires otherwise, patient authorization is necessary for the disclosure of information contained in medical records to third parties.